A tribe hidden in plain sight: the ambiguous role of the instructor in a Caribbean university. Issue 3 (4th May 2019) - Blair, Erik; Briggs, Georgette
ABSTRACT: The unbundling of the higher education sector has led to an increase in the number of academic tribes. One such tribe is that of the 'instructor'. This paper examines how instructors at a university in Trinidad and Tobago are conceptualised at the institutional and individual level. Three data sources were examined: a document review of role descriptions as found in job adverts; quantitative self-perception data and qualitative data on perceptions of job roles. Analysis of the data shows that instructors undertake many of the same roles as lecturers but that this is not recognised in institutional documentation. This local analysis finds that instructors form an academic tribe whose activities appear to be hidden in plain sight. Such a position is likely to have managerial and/or policy implications leading to a re-examination of 'teaching-only' positions which may, in turn, result in a move back towards a re-bundled academic identity.